The impact of macroeconomic variables towards gross domestic product in Malaysia / Suraya Roslan - Roslan, Suraya (2016)
This paper is made to find out about the impact of macroeconomic variables towards gross domestic product. By using secondary data for this analysis is retrieve from other journal, article and data stream. Sample data for this study selected from data stream on over fifteen years started from January 2001 to December 2015. The methodology used for this study is by using the Multiple Linear Regression with Eviews sourced from Data Stream. In this study, the dependent variable is gross domestic product, while independent variable is macroeconomic variables. Based on the variables, the purpose of the study is to investigate the impact between macroeconomic variables on the gross domestic product in Malaysia for fifteen years started from January 2001 until December 2015. In addition, this research like to explore the effect of macroeconomic variables examples inflation (CPI), interest rate (BLR), import and export to gross domestic product. The result indicates that there is co-integrated between the macroeconomic variables and gross domestic product. The result of this study is hoped to help investor, financial analyst and academician to identify the step that should be taken before make the decision about investment decisions.